2015
DOI: 10.1515/cclm-2014-0520
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases as biomarkers of disease: updates and new insights

Abstract: Matrix metalloproteinases (MMPs) play a pivotal role in remodeling the extracellular matrix (ECM) and are therefore of interest for new diagnostic tools for the clinical management of diseases involving ECM disruption. This setting ranges from the classical areas of MMP studies, such as vascular disease, cancer progression or bone disorders, to new emerging fields of application, such as neurodegenerative disease or sepsis. Increasing the knowledge about the role of MMPs in the pathogenesis of diseases where a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 14 publications
1
70
0
Order By: Relevance
“…MMP family proteolytic enzymes are indispensable for the remodeling of extracellular matrix, of which the degradation is a prerequisite for the invasion and metastasis of cancer (27,28). In the present study, it was demonstrated that the protein expression level of MMP2 was notably decreased following miR-766-5p inhibitor treatment compared to that following treatment with the NC.…”
Section: Discussionsupporting
confidence: 45%
“…MMP family proteolytic enzymes are indispensable for the remodeling of extracellular matrix, of which the degradation is a prerequisite for the invasion and metastasis of cancer (27,28). In the present study, it was demonstrated that the protein expression level of MMP2 was notably decreased following miR-766-5p inhibitor treatment compared to that following treatment with the NC.…”
Section: Discussionsupporting
confidence: 45%
“…MMP-2 and MMP-9 are tightly regulated at the levels of transcription and secretion by multiple factors. For example, various stimulating factors can trigger MAPK, NF-jB and PYC signaling pathways, leading to effects on the GC box in the MMP-2 promoter region or to effects on AP-1 and NF-jB binding to the MMP-9 promoter region for expression regulation (Gallera et al, 2015). Therefore, in this study, we further speculated that curcumin likely down-regulated the transcription and inhibited the secretion of MMP-2 and MMP-9 by triggering MAPK and NF-jB, which ultimately caused partial suppression of SHI-1 cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…[5]. They are important in creating an environment that support the initiation and maintenance of growth of primary and metastatic tumors, and have an important regulatory role, as they can modulate cytokines and chemokines activity by proteolytic processing [6].…”
Section: Introductionmentioning
confidence: 99%